Health Risk Assessment of PET Bottles in GCC - Mortula, Maruf (2013)
Bottle water is getting very popular all through the world; especially in the gulf countries as the main source of drinking water. However, concerns over leaching of toxic chemicals are increasing. In this study, a health risk assessment was conducted in accordance with the guidelines indicated by United States Environmental Protection Agency (USEPA). It is conducted based on leaching of Diethyl Phthalate (DEP) from Polyethylene terephthalate (PET). The toxicity and exposure assessment of diethyl phthalate was conducted to characterize its risk on human health. Risk management is also discussed.